UNDERSTANDING THE MEANING OF WELL-BEING IN THE PERSPECTIVE OF PSYCHOLOGICAL SCIENCE: A LITERATURE REVIEW - Rinandita Wikansari; Abu Muna Almaududi Ausat; Silvy Sondari Gadzali; Suherlan Suherlan; Hizbul Khootimah Azzaakiyyah (Community Development Journal : Jurnal Pengabdian Masyarakat, 2023)
Work is hard, but if it is carried out with joy or it can be said that if you like the work you do, then the person is in a state of well-being. This study aims to explain the dimensions of well-being in detail so that it can be used as the main reference for further research that has special attention to the meaning of well-being in the perspective of psychology. This literature review article develops a conceptual framework on the dimensions of well-being. Based on the literature review, this research arrives at the finding that there are six dimensions of well-being which are the essence of positive functioning psychology theories ranging from self-acceptance, autonomy, environmental mastery, positive relationships, purpose in life, and personal growth. The research methodology and arguments that accompany this study can help advance discussions in psychology, management, and business administration courses. This research has important implications for future studies that use quantitative, qualitative, and mixed methodologies.